The impact of home storage conditions on the accumulation of acrylamide precursors in potato tubers. (20th August 2020) - Ducreux, Laurence J. M.; Pont, Simon D. A.; Verrall, Susan R.; McManus, William; Hancock, Robert D.; Taylor, Mark A.
Abstract: The aim of this work was to investigate the impact of domestic storage conditions on total reducing sugars and free asparagine in fresh potatoes to understand the implications for acrylamide‐forming potential. Current advice to consumers is that potatoes should be stored in a dark cool place, but not in the refrigerator based on an expectation that home storage in the refrigerator will result in "cold sweetening" and increased acrylamide‐forming potential. Potato tubers of two common varieties (King Edward and Nectar) were obtained from four independent sources and were sampled from commercial store conditions on three occasions between November 2018 and May 2019. Tuber reducing sugar contents were assessed under conditions that mimicked home storage, at either 18 or 5°C during a 15‐day treatment period. There was a similar pattern of reducing sugar content in tubers from all four sources. For tubers stored at 5°C, reducing sugar levels showed little or no variation over the 15‐day time‐course. Differences in reducing sugar contents between varieties and between the source of tubers of the same variety were far higher than those observed dependent on cold storage. For tubers stored at 18°C, total reducing sugar levels remained the same or decreased over 15 days of storage. Decreases in sugar content were not consistent between samples, varying by sampling point, source and cultivar. Tuber asparagine content was independent of storage temperature with no significant differences in asparagine observed between tuber samples stored at 5 or 18°C for 15 days. In some tuber samples, storage at 5°C significantly retarded sprouting compared with samples stored at 18°C, indicating the potential for refrigerator storage to extend shelf life and reduce waste. The premise that home storing potato tubers at 5°C postpurchase increases levels of reducing sugars and therefore acrylamide‐forming potential is not supported by these data. Much larger sources of variation were from other factors. Abstract : Simulated home storage of potatoes at 5 or 18°C suggests that there is little risk of reducing sugar accumulation following home storage of tubers in the refrigerator. These data indicate no additional risk of acrylamide formation in home‐cooked potatoes following cold storage and highlight the opportunity to reduce the large volumes of potatoes discarded by UK consumers.